2016
DOI: 10.1039/c6cp02971j
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature excitonic spectroscopy and dynamics as a probe of quality in hybrid perovskite thin films

Abstract: We have developed a framework for using temperature dependent static and dynamic photoluminescence (PL) of hybrid organic-inorganic perovskites (PVSKs) to characterize lattice defects in thin films, based on the presence of nanodomains at low temperature. Our high-stability PVSK films are fabricated using a novel continuous liquid interface propagation technique, and in the tetragonal phase (T > 120 K), they exhibit bi-exponential recombination from free charge carriers with an average PL lifetime of ∼200 ns. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…4 Further, our finding provides a natural explanation of the fact that charge carrier lifetimes in PV perovskites decrease with temperature, a striking property which stands in stark contrast to classic semiconductors, such as Si or GaAs, in which charge recombination is a phonon-driven process and is thus hampered at lower temperatures. [45][46] More specifically, below 120 K charge carrier lifetimes were observed to drop abruptly, by an order of magnitude, consistent with freezing of the whole-body reorientation of the cation, as determined from 2 H spectra in this work. Other work 47 has reported that the fill factor (FF) of a MAPbI3-based cell decreased roughly linearly with temperature, by a factor of 2.6 between 300 and 100 K, and led to a similar trend in the photovoltaic efficiency (PCE) (decrease by a factor of 3 between 300 and 100 K).…”
Section: Probing Dynamics Of Individual Cations In Native Doublecatiosupporting
confidence: 84%
“…4 Further, our finding provides a natural explanation of the fact that charge carrier lifetimes in PV perovskites decrease with temperature, a striking property which stands in stark contrast to classic semiconductors, such as Si or GaAs, in which charge recombination is a phonon-driven process and is thus hampered at lower temperatures. [45][46] More specifically, below 120 K charge carrier lifetimes were observed to drop abruptly, by an order of magnitude, consistent with freezing of the whole-body reorientation of the cation, as determined from 2 H spectra in this work. Other work 47 has reported that the fill factor (FF) of a MAPbI3-based cell decreased roughly linearly with temperature, by a factor of 2.6 between 300 and 100 K, and led to a similar trend in the photovoltaic efficiency (PCE) (decrease by a factor of 3 between 300 and 100 K).…”
Section: Probing Dynamics Of Individual Cations In Native Doublecatiosupporting
confidence: 84%
“…[41,42] Furthermore, annealing for long time periods has been observed to lead to PVSK decomposition due to the formation of PbI 2 . [43,44] Expectedly, these samples show significantly modified properties. The PVSK thin film deposited on ITO glass appears to be optically almost "dark", and PL is progressively enhanced by the nano-structured, single crystalline, and micro-structured ZnO layers [Figure S4(a)], in that order.…”
Section: Pvsk Thin Film and Zno Layer Interface Characteristicsmentioning
confidence: 94%
“…N tot is the total charge carrier density, directly proportional to the excitation power P, implying for free charge carriers and for excitonic recombination. Therefore, by fitting a second order polynomial to the power dependent PL of PVSK at any fixed temperature T [Figure S5], the quadratic and linear coefficients corresponding to free charge carriers and excitons [25,44] at that T can be This article is protected by copyright. All rights reserved.…”
Section: Exciton Recombination In Pvsk Tuned By Zno Layersmentioning
confidence: 99%
See 2 more Smart Citations